THE CORRELATION OF INTEREST IN PLAYING OUTBOUND WITH CONFIDENCE CHILDREN AGED 5-6 YEARS (BELIA: Early Childhood Education Papers, 2022)
Play is an important activity for children. Through play, children can learn about new things and develop various abilities. One of the activities that can be done is playing outbound. Outbound activities can stimulate children to push competition between one child and another, develop courage and develop the physical, motoric and social emotional aspects of children. However, there are still many children who are afraid to try outbound because they are not confident in their abilities. This study aims to identify the correlation between interest in playing outbound with the self-confidence of children aged 5-6 years on the De Bale Cingkrong Purwodadi playground. The method of this study uses quantitative methods with questionnaires, interviews, and documentation as instruments in data collection. The results showed that there was a significant relationship between interest in playing outbound with children's self-confidence in the de bale Cingkrong Purwodadi playground. The results also reveal that parents have an awareness that children need the freedom to explore various activities, one of which is by playing outbound. Keywords: playing outbound, self-confidence.